The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1164/arrd.1986.133.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Enzyme Immunoassay, Immunodiffusion, and Complement Fixation Tests in Detecting Antibody in Human Serum to the A Antigen ofBlastomyces dermatitidis1–3

Abstract: Using a new enzyme immunoassay (EIA) and standard immunodiffusion (ID) and complement fixation techniques for antibody to the A antigen of Blastomyces dermatitidis, we tested serum from 27 patients with blastomycosis diagnosed histopathologically or by culture; 20 with diagnoses made during 1981 through 1983 (Group A) and 7 during 1974 through 1976 (Group B). We also studied 30 control subjects with Mycoplasma pneumoniae infection (17 subjects), histoplasmosis (6 subjects), coccidioidomycosis (1 subject) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 0 publications
0
51
0
Order By: Relevance
“…10 histoplasmosis patients had acute pulmonary infection, 10 had chronic pulmonary disease, and 4 had disseminated disease; no clinical information was available in the remaining 10 histoplasmosis patients. 7 coccidioidomycosis patients had acute pulmonary infection, 5 had chronic pulmonary disease, and 10 had disseminated disease. 10 sporotrichosis patients had isolated cutaneous disease and 1 had cavitary pulmonary disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 histoplasmosis patients had acute pulmonary infection, 10 had chronic pulmonary disease, and 4 had disseminated disease; no clinical information was available in the remaining 10 histoplasmosis patients. 7 coccidioidomycosis patients had acute pulmonary infection, 5 had chronic pulmonary disease, and 10 had disseminated disease. 10 sporotrichosis patients had isolated cutaneous disease and 1 had cavitary pulmonary disease.…”
Section: Methodsmentioning
confidence: 99%
“…Both antigens are impure (5,6), they appear to be a mixture ofcell wall components, and tests employing them are not widely available. A further problem with serologic tests using A antigen has been diminished specificity as sensitivity is increased by enzyme immunoassay techniques (7)(8)(9). This problem results from A-antigen impurity and the extensive sharing of cell wall components between dimorphic fungi, particularly B. dermatitidis and Histoplasma capsulatum.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of blastomycosis is usually based upon direct visualization of broad-based budding yeast in a clinical specimen or culture of the organism (3)(4)(5)(6)(7). The methods can be time-consuming or require invasive procedures.…”
mentioning
confidence: 99%
“…According to a recent review, an agar gel immunodiffusion (AGID) test showed a sensitivity of only 32%, and in previous studies less than half of blastomycosis cases were seropositive (6)(7)(8)(9)(10)(11). Complement fixation is less sensitive than AGID in patients with blastomycosis, is more difficult to perform, and offers no advantages over AGID (7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation